2000
DOI: 10.1021/jp000016b
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of Linear and Nonlinear Optical Properties of H−Silsesquioxanes

Abstract: We report the frequency dependence of linear and nonlinear optical susceptibilities of H-silsesquioxanes of various cage sizes and conformations using the INDO/CI method coupled with the SOS method. The average dynamic refractive index of silsesquioxanes is found to decrease as the cage size increases, and its variation is very small for the different conformations of the same cage size at the same incident wavelength. The calculated second-order susceptibilities show that small cages have a larger magnitude w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…The supernatant containing apoFd was obtained by centrifugation of the lysate at 8000Ug for 15 min. Chemical reconstitution of Fd was carried out essentially according to the method described previously [25,26]. Urea (biochemical grade) was added to the supernatant to a ¢nal concentration of 8 M. Under a stream of argon gas, the solution was gently stirred for 40 min at room temperature after DTT was added to a ¢nal concentration of 100 mM.…”
Section: Culture Of Bacterial Cells Reconstitution and Puri¢cation Ofmentioning
confidence: 99%
“…The supernatant containing apoFd was obtained by centrifugation of the lysate at 8000Ug for 15 min. Chemical reconstitution of Fd was carried out essentially according to the method described previously [25,26]. Urea (biochemical grade) was added to the supernatant to a ¢nal concentration of 8 M. Under a stream of argon gas, the solution was gently stirred for 40 min at room temperature after DTT was added to a ¢nal concentration of 100 mM.…”
Section: Culture Of Bacterial Cells Reconstitution and Puri¢cation Ofmentioning
confidence: 99%
“…It received much attention after its unique applications as carbonless protective coatings and interlayer dielectrics were successfully demonstrated in the early 1990s for the semiconductor industry [2][3][4]. The growing interest in H-resin is evidenced by the increasing number of studies published in the external literature, from both experimental and theoretical investigations [5][6][7].…”
mentioning
confidence: 99%
“…For the calculation of ␥, we generally truncate the infinite SOS expansion to a finite one after apparent convergence of ␥ has been reached. 32 Kim et al 33 observed silsesquioxane oligomers with various alkyl substituents using a graphite plate laser desorption/ionization time-of-flight mass spectrometry ͑GPLDI-TOF-MS͒ method and concluded that the nature of the organic substituents plays an important role in determin-ing the microstructure of polysilsesquioxanes. It is found that the segments of the curves are smooth at lower energy states.…”
Section: Dynamic Third-order Polarizabilitiesmentioning
confidence: 99%